Cerebral hemodynamics in children with sickle cell disease in India: An observational cohort study. Issue 27 (8th July 2022) - Gajjar, Bhakti; Sharma, Sanjay; Khan, Erum; Sharma, Pranita; Jain, Pawan; Goel, Vikas; Neral, Arvind; Patel, Jyotish; Parmar, Mamta; Sharma, Kanika; Sharma, Vijay K.; Sharma, Arvind K.
Abstract : India has the second highest number of cases of sickle cell disease (SCD) and affects the most socioeconomically disadvantaged communities living in a horizontal belt from Gujarat to Odisha state. Despite high prevalence, information about cerebral hemodynamics among children with SCD in India remains scarcely described. We performed transcranial Doppler (TCD) to assess cerebral hemodynamics among Indian children with SCD and evaluated their association with clinical and hematological parameters. Children aged 3-18years, diagnosed with SCD living in Raipur in Chhattisgarh and Ahmedabad in Gujarat state were recruited. TCD was performed to obtain flow velocities from middle cerebral (MCA), intracranial internal carotid (ICA) and basilar artery. Associations were evaluated between timed-average-mean-maximum velocities (TAMMV) and various clinical and hematological parameters. Our prospective study included 62 consecutive children with known SCD. Mean ± SD age of the study population was 9.8 ± 3.9 years and 31 (50%) were male. Mean ± SD hemoglobin was 8.64 ± 1.34 Gm/dL while the mean HbSS ± SD was 70.25 ± 15.27%. While 6 (9.6%) children had suffered from stroke during previous 2 years, 7 (11%) demonstrated abnormal TAMMV. Higher HbSS level along with history of iron chelation therapy, blood transfusion and/or stroke showed a trend towards having higher TAMMV. Stroke and cerebral hemodynamic alterations are common among Indian children with SCD. Larger studies with detailed neuroimaging and genetic evaluations are needed for better understanding, characterization, risk stratification as well as optimization of the timing of blood transfusion to reduce physical disabilities among Indian children with SCD.